Analysis Of Comparative Results Of Standing Waves Between Waves On Guitar Strings And Waves On Strings - Wafiyah, Dzihni; Mauliddy , Hikmah; Ikhfas Tanzilal , Muhammad; Suryadi , Ahmad; Hernawati Kusuma , Fuji (PT. ALHAFI BERKAH INDONESIA, 2023)
This research aims to analyze the comparison of standing wave results between waves on a guitar string and waves on a cord. The study is conducted through two separate experiments, focusing on understanding the relationship between wave velocity and tension on the string, understanding the relationship between wave propagation speed and mass per unit length on the string, and analyzing the comparison of standing wave results. The first experiment is focused on observing the changes that occur as the tension value on the string increases. Meanwhile, the second experiment is designed to observe the tight binding of the string’s mass and the propagation speed of sound waves. Standing waves, also known as standing waves, emerge as a result of interference between two waves with the same frequency and amplitude but different propagation directions. The amplitude peak occurs at the node, while the antinode indicates the minimum amplitude. Essentially, waves are generated from a string attached to a vibrator.